The Relation Between Church and Politics - David Ming (Jurnal Didaskalia, 2020)
The relationship between the Church (religion) and politics is a very important matter to be discussed both in the academic sphere and in the scope of society in general. The relationship is different from time to time as the relationship between the two raises a polemic. This is due to the understanding that the field of service the church must be restricted to theological matters. On the other hand, there are those who hold that church activities cannot be narrowed only to abstract / theological matters. The church must instead show its concern on social issues that are very concrete, for example political issues. But before we enter into the discussion of the relationship between "Church and Politics", it helps us to understand what church and politics are